DRAMATARI SEBAGAI RUANG GUGATAN NARASI: IMPLEMENTASI PENDEKATAN 4R DALAM PENCIPTAAN DRUHYARING SATYA - Tyoba Armey Astyandro Putra; Deri Al Badri; Eti Mulyati (Greget: Jurnal Kreativitas dan Studi Tari, 2026)
Learning dramatari in higher arts education can no longer be understood merely as a process of transferring movement techniques and reproducing traditional performance forms. This study aims to (1) describe the transformation of dramatari learning at the Dance Department of Institut Seni Budaya Indonesia (ISBI) Bandung through the 4R approach—revisiting, requestioning, reinterpretating, and recreating—developed by Eko Supriyanto; (2) analyze the implementation of this approach in the dramatari performance Druhyaring Satya; and (3) identify its impact on students' creativity and artistic awareness. This research employed a qualitative descriptive method with a practice-based research approach, involving 27 students in a sixth-semester dramatari course during the 2025/2026 academic year. Data were collected through participatory observation, performance documentation, script analysis, and reflective writings from 27 students using a structured reflection guide. The findings indicate that the 4R approach successfully shifted the learning process from reproductive to exploratory, collaborative, and reflective. The performance Druhyaring Satya—60 minutes in duration, involving 27 dancers including double casting performers, staged at the Sunan Ambu Arts Building of ISBI Bandung on 19 May 2026—served as concrete implementation of this transformation through the reinterpretation of the Perang Bubat historical narrative as a critical interrogation of collective memory shaped by colonial historiography. Thematic analysis of 27 students' reflective writing identified five transformation themes: novelty of form, courage to leave familiar artistic zones, process intensity as bodily experience, collective work and artistic negotiation, and critical questioning of tradition and history.